How life works - Matthews, Andrew (Seashell Publishers, 2015)
A fun, whimisical primer to the New Thought movement. THE MYTH: Success makes you happy. THE FACT: Happiness makes you successful. It's not about who you know, or even what you know. It's about how good you feel, which, luckily for you, is entirely within your own power. Discover how to feel good, replace patterns of fear and failure with love and kindness, and create the life of abundance you've always dreamt of: * Doing work you love * Surrounded by people you love * And with the love of your life'In a Nutshell' features throughout provide useful reminders of the key valuable lessons in each chapter. How Life Works is illustrated with 90 of Andrew's trademark sketches. "My cartoons illustrate the message", says Andrew. "Cartoons also remind us not to take life too seriously."